2024
DOI: 10.3390/insects15020101
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of the Effect of Pollen Substitute Diets on Honey Bees during Early Spring

Hyunjee Kim,
Olga Frunze,
Abdulkadir Yusif Maigoro
et al.

Abstract: The nutritional quality of a colony significantly affects its health and strength, particularly because it is required for population growth in the early spring. We investigated the impact of various artificial pollen substitute diets on colony performance in the Republic of Korea during early spring, a critical period for colony health and growth. The colonies were provided with different diets, including the commercial product Megabee (positive control), our developed diet Test A, and four upgraded versions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…The experimental results presented in this study provide valuable information on the response of colonies (consumption) and individual honey bees (Vg, HPG, and ALC) to different pollen substitute feeds. Consumption is an important indicator for understanding the quality and effects of a diet and can be influenced by several characteristics (colony and diet) [33]. Our results showed that the pollen substitute diet prepared with fresh pollen and spirulina was consumed to a higher extent by the bees during the experimental period.…”
Section: Diet Consumptionmentioning
confidence: 69%
See 3 more Smart Citations
“…The experimental results presented in this study provide valuable information on the response of colonies (consumption) and individual honey bees (Vg, HPG, and ALC) to different pollen substitute feeds. Consumption is an important indicator for understanding the quality and effects of a diet and can be influenced by several characteristics (colony and diet) [33]. Our results showed that the pollen substitute diet prepared with fresh pollen and spirulina was consumed to a higher extent by the bees during the experimental period.…”
Section: Diet Consumptionmentioning
confidence: 69%
“…In the determination of the pH values, 2 g of the diet samples was dissolved in 15 mL of distilled water and measured after a waiting period of 24 h [33,34]. The nutrient content of the diets is given in Table 3.…”
Section: Chemical Analyzes Of Dietsmentioning
confidence: 99%
See 2 more Smart Citations
“…The detailed components and concentrations of each diet are listed in Table 1. Diet 2 and Diet 3 were selected based on their positive colony performance in our previous study [26]. Diet 1 was a blend of ingredients aimed at enhancing the functions of Diet 2 and Diet 3.…”
Section: Preparation Of Pollen Substitute Dietmentioning
confidence: 99%